Olavo de Carvalho and the rise of the Far Right - Calil, Gilberto (Argumentum, 2021)
This article analyses Olavo de Carvalho’s pathway and reflects on his role in advancing the Far-Right in Brazil. To this end, it discusses his trajectory and his strategies for spreading his positions, with an emphasis on the website Mídia sem Máscaras (MSM) (Media without masks). A proposed “cultural war” and the denunciation of the supposed “Gramsci-ist” influence are central elements of this process. Finally, the article approaches the relationship between Olavo de Carvalho and the Bolsonaro family and their influence within the current Brazilian government.